(C7H20N2)[(UO2)(2)(SO4)(3)(H2O)]: an organically templated uranium sulfate with a novel layer topology - Norquist, A; Doran, M; O'Hare, D (2005)
The title compound, poly[N,N,N′N′-tetramethylpropane-1,3-diaminium [aquatetraoxotri-μ3-sulfatodiuranate(VI)]], (C7H 20N2)[(UO2)2(SO4) 3(H2O)]n, contains two-dimensional [(UO 2)2(SO4)3(H20)] 2~ layers that are unprecedented in uranium chemistry. The layers in this compound are separated by C7H20N22+ cations, forming the basis of an extensive hydrogen-bonding network. An independent intralayer hydrogen-bonding network is also observed, involving water molecules bound directly to a uranium centre. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.